Effect of Competence on Employee Performance on Id Express Sumedang - Faisal Ramdhani; Risa Ratna Gumilang; Ila Karmila (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2022)
The core problem of this research is the less than optimal working power of employees. The purpose of the study was to determine the implementation of competence, employee performance, and the magnitude of the influence of competence on employee performance at ID Express Sumedang. This study uses a descriptive research method approach with quantitative analysis techniques, conducted through a survey method. Data collection techniques were analyzed by means of observation and questionnaires. The population of employees at ID Express Sumedang is 40 people and the research sample is 40 people. The research data uses simple regression analysis, correlation test, coefficient of determination and hypothesis testing. The results showed that the implementation of competence was 2,394 (very good) with an average of 85.50%, employee performance was 2,407 (very good) with an average of 85.96%, then the strong relationship between competence and employee performance at the ID Express Office Sumedang is 0.832 (strong relationship), and the magnitude of the influence of competence on employee performance at the Sumedang ID Express Office is 69.2% and there are still 30.8% other factors. The results of the hypothesis test, it turns out that tcount (9.24) > ttable (1.68595), it can be said that there is a positive influence between competence on employee performance at the Sumedang ID Express Office which is acceptable. To improve one's performance, employees have basic characteristics because individual characteristics are a deep and inherent part of a person